The Rights and Obligations of the Sending State and its Military Forces upon the Establishment of Military Bases - Peshraw Hamajan Aziz; Bzhar Shawkat Karem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The presence of military bases in host countries is linked to several factors, as the strategic, geological and political dimension of the host country is an important factor in the presence of such bases on its territory, and their presence results in many positive effects, such as establishing factories or practicing specific activities to provide the needs of those bases, and constructing structures. Infrastructure and its maintenance and the establishment of commercial, residential, military and other complexes. On the other hand, there are negative effects such as the financial burdens resulting from hosting these bases, and the catastrophic effects that affect the economy or facilities as a result of war or sabotage, whether on the construction or humanitarian level. The deployment of foreign forces on the territory of another country has an impact on a range of issues such as the economy, development, trade, foreign investment, crime, human rights, public opinion, and foreign policy in the host country. There is also the impact of the deployment of American forces on the level of the host country’s forces and Military expenditures and participation in the conflict, the deployment of forces in this way is not limited to the host country only, but also has an indirect impact on the country neighboring the host country. The topics included in all agreements are in order to achieve a balance between the interests of the two countries. For this reason, the host state gave rights to the sending state in order for its base to operate efficiently and easily, and therefore it must be given within the limits of what is present in the agreements concluded by it and which the host state controlled, and the obligations must be to a degree so that the sending state can maintain them, Regular joint committees must be formed to prevent corruption from affecting them.